2014
DOI: 10.1007/s13762-014-0706-9
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of tetracycline using nanosized titanium dioxide in aqueous solution

Abstract: The aim of the study was to investigate the degradation kinetics of tetracycline antibiotic by nanosized titanium dioxide under ultraviolet irradiation. Enhancement of photocatalysis by addition of Hydrogen peroxide was also evaluated. Various experimental parameters such as initial tetracycline concentrations, initial titanium dioxide concentration, initial pH, reaction times, initial Hydrogen peroxide concentrations, as well as water matrix using ultrapure water, drinking water and secondary effluent were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(93 citation statements)
references
References 69 publications
10
83
0
Order By: Relevance
“…This figure clearly indicates that the absorbance of the band located at 368 nm decreases with the reaction time indicating rupture of phenolic groups to aromatic rings B, also shows that the absorbance of the bands located at 270 nm decrease with reaction time, we can attribute this to the production of acylamino and hydroxyl groups. These results suggest that they are a by-product, which is more recalcitrant and therefore difficult to eliminate at 100% 30,31 .…”
Section: Photocatalytic Activitymentioning
confidence: 97%
“…This figure clearly indicates that the absorbance of the band located at 368 nm decreases with the reaction time indicating rupture of phenolic groups to aromatic rings B, also shows that the absorbance of the bands located at 270 nm decrease with reaction time, we can attribute this to the production of acylamino and hydroxyl groups. These results suggest that they are a by-product, which is more recalcitrant and therefore difficult to eliminate at 100% 30,31 .…”
Section: Photocatalytic Activitymentioning
confidence: 97%
“…Similar finding have been reported by Usharani et al, 14 and by Gar Alalma et al 15 These authors have reported first order reaction kinetics for the degradation and mineralization of chlorinated pesticides and insecticides and other various water pollutants by photocatalytic ozonation. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The results, shown in figure 5, demonstrates that the optimal conditions for imazapyr degradation with photocatalytic ozonation is neutral pH. On the other hand, the combination of two oxidation systems, ozonation and photocatalysis, for water treatment under optimal conditions are reported to have increased oxidation efficiencies (synergy) compared to the sum oxidation efficiencies of these two oxidation systems separately.…”
Section: Effect Of Ph Influence On Imazapyr Degradationmentioning
confidence: 98%
“…A possible explanation resides in the fact that as imazapyr concentration rises, it is possible that more organic substances are deposed on the surface of TiO 2 , whereas less number of photons are available to reach the catalyst surface and the probability of reaction between imazapyr molecules and oxidizing species also decreases, thus resulting in less degradation percentage. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] …”
Section: Effect Of Initial Herbicide Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of photocatalytic reactions is that if the semi-conductive particles are irradiated with high-energy radiation, high-energy electron pairs and holes are formed; these generated electron pairs -holes are the initiator of oxidation -reduction process through the production of free radicals, and finally they lead to the mineralization of organic compounds emissions. One of the most important semiconductors is TiO 2 , which is an affordable, available, non-toxic, and very high performance semiconductor (18). Reyes et al (2006) studied the removal of tetracycline antibiotic using TiO 2 nanoparticles under UV irradiation and concluded that in general the use of photocatalytic refinement can be used as an interesting topic in degradation of tetracycline antibiotic and replacement of existing conventional.…”
Section: The Effect Of Ultrasound (Us) and Uv On Antibiotics Removalmentioning
confidence: 99%